2014
DOI: 10.1371/journal.pone.0090007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dosimetric Feasibility of Hippocampal Sparing Intensity-Modulated Radiotherapy in Patients with Locally Advanced Nasopharyngeal Carcinoma

Abstract: PurposeThe objective of this study was to evaluate the dosimetric feasibility of using hippocampus (HPC) sparing intensity-modulated radiotherapy (IMRT) in patients with locally advanced nasopharyngeal carcinoma (NPC).Materials/MethodsEight cases of either T3 or T4 NPC were selected for this study. Standard IMRT treatment plans were constructed using the volume and dose constraints for the targets and organs at risk (OAR) per Radiation Therapy Oncology Group (RTOG) 0615 protocol. Experimental plans were constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…These biological macromolecules can be detected in the peripheral blood. Thus, serum EA-IgA and VCA-IgA expression could be detected clinically to evaluate nasopharyngeal carcinoma lesions level [ 13 15 ]. In this study, we tested the 2 index expression levels mentioned above in human serum to investigate its correlation with clinical nasopharyngeal carcinoma staging and provide basis for early clinical staging diagnosis of nasopharyngeal carcinoma in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These biological macromolecules can be detected in the peripheral blood. Thus, serum EA-IgA and VCA-IgA expression could be detected clinically to evaluate nasopharyngeal carcinoma lesions level [ 13 15 ]. In this study, we tested the 2 index expression levels mentioned above in human serum to investigate its correlation with clinical nasopharyngeal carcinoma staging and provide basis for early clinical staging diagnosis of nasopharyngeal carcinoma in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, not little evidence suggests that impaired hippocampal neurogenesis resulting from cranial irradiation [ 10 13 ] should be strongly associated with NCF impairment [ 9 , 14 ]. Moreover, a few studies demonstrated that the isodose distribution irradiating the hippocampus is definitely related to NCFs after cranial irradiation in patients with primary brain tumors [ 15 17 ] or in those with nasopharyngeal carcinoma [ 18 , 19 ]. As a result, it has been hypothesized that conformal hippocampal sparing during the course of WBRT (HS-WBRT) would provide meaningful preservation in terms of cognitive function [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean dose was also considered as a parameter that should be considered for developing hippocampal‐sparing strategies in patients undergoing WBRT followed by radio‐surgical boost or WBRT and simultaneous integrated boost treated with VMAT. Hippocampal avoidance strategies have been also implemented for locally advanced nasopharyngeal carcinoma and in radiosurgery of multiple intracranial targets using Gamma Knife Perfection ® equipment . Both studies confirm the reduction in mean hippocampal dose up to 35% in hippocampal‐sparing replanned cases, maintaining the same conformity and target coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal injuries play a fundamental role both in short and long‐term memory loss and cognitive impairment . Cranial irradiation can induce hippocampus damage, as suggested by some studies . In particular, cognitive impairment caused by whole brain irradiation (WBRT) has been investigated .…”
Section: Introductionmentioning
confidence: 99%